How to write up and publish your scientific research - Macnab, Andrew John (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2022)
There are many reasons to write a paper. Your reason ‘why' will be personal and uniquely yours. You may well have had an innovative idea or collected novel research data, discovered new information of importance, or found a better way to do something; it maybe you are in a profession where it is an expectation that you ‘publish' as part of your career path. Whatever the reason, knowledge transfer through peer reviewed publication is an integral part of academic activity and the advancement of science, so many of us find ourselves faced with the task of writing a paper and submitting it for publication. This editorial provides the general formula that most scientific papers follow, and the sections that make up an article. The anatomy of a successful scientific paper includes Title, Abstract, Keywords, Introduction, Materials/Methods, Results, Discussion and Conclusion. Each journal also has its own requirements for formatting and content that define its style, so it is essential to read the journal's ‘Guidelines for Authors' to get detailed instructions on all aspects of how to set out your paper; these are available online; for example for the Global Health Management Journal, go to: https://publications.inschool.id/index.php/ghmj. Writing a paper is never easy, but it can be straightforward if you follow the established guidelines; remember Asher's six words for framing your manuscript, and, include the elements required in each section of the paper. Writing a paper is best not done alone. Gather ideas, thoughts and encouragement from your co-authors and supervisor/colleagues; have someone not connected with the work you have done read what you have written to make sure it is easy to understand (and interesting). We all learn from reading papers other authors have written in good journals, and from the feedback we receive through reviewer's comments/suggestions on what we have written. When your paper is published, remember to pause and celebrate your success, as being published is an achievement, and only happens after a lot of hard work. Then, once you are an author, keep writing! Also, act as a mentor to the friend or colleague who asks you,